2020
DOI: 10.3390/ijerph17030781
|View full text |Cite
|
Sign up to set email alerts
|

Deficit Alternate Drip Irrigation Increased Root-Soil-Plant Interaction, Tomato Yield, and Quality

Abstract: To determine the soil mechanism in root-zone caused by water saving and the production response to alternate drip irrigation (ADI), the present study investigated the effects of deficit ADI on tomato growth using the conventional surface drip irrigation (CDI) as a control. The interactions among the experimental treatments on root index, photosynthetic efficiency, biomass accumulation, yield, fruit quality and irrigation water use efficiency (IWUE) were assessed and the inner mechanism of root-soil effecting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
1
9
2
Order By: Relevance
“…Such inconsistency is probably due to the difference of irrigation amount. In this study, the minimum amount is 73.46 mm, which is lower than that of Wang's study, and the highest amount is 218.42 mm, which is higher than that of Wang's study [40].…”
Section: Effects Of Different Treatments On Fruit Quality Of Tomato I...contrasting
confidence: 73%
“…Such inconsistency is probably due to the difference of irrigation amount. In this study, the minimum amount is 73.46 mm, which is lower than that of Wang's study, and the highest amount is 218.42 mm, which is higher than that of Wang's study [40].…”
Section: Effects Of Different Treatments On Fruit Quality Of Tomato I...contrasting
confidence: 73%
“…It should be noted that nutrient uptake affects the tomato production by increasing mineral contents, flower clusters, fruit set percentage, and reducing physiological disorders leading to higher yield [37]. The current results are in agreement with the findings of [34] who showed that an increase in root surface area enhances nutrient uptake leading to increased total yields and the number of fruits per plant [38,39] also reported the highest crop yield per hectare after earthing up potato 15 days after complete plant emergence. Nutrients not only increase the yield of tomato by reducing the flower drop but also increase the fruit retention [40].…”
Section: Effect Of Earthing Up Levels and Pruning System On Tomato Yisupporting
confidence: 92%
“…Earthing up probably caused an increase in the circulation of oxygen in the root zone enhances the development of mitochondria and proteins in the root cell leading to an increase in plant growth and development [28]. In this context, it will be expected that any positive impact on growth is as a result of increasing earthing levels, improved soil aeration and consequently root hair development [34]. Proper root development promotes efficient nutrient uptake and partitioning to the productive suckers and trusses in tomatoes [35].…”
Section: Effect Of Earthing Up Levels and Pruning System On Tomato Yimentioning
confidence: 99%
“…In addition, the half plastic covering can significantly promote root-soil-microorganism interactions and enhance the nutrient uptake by plant roots [29], which will indirectly affect and improve Pn. In this study, it was found that the half plastic covering increased the total fresh biomass by 5.65% and 24.15%, respectively, compared with the full covering and no plastic covering.…”
Section: Half Plastic Covering Was Beneficial To Pn and Fresh Biomassmentioning
confidence: 99%